Plant growth and health promoting bacteria - Maheshwari, D. K.; SpringerLink (Online service). (Heidelberg New York Springer, 2010)
To cope with the increasing problems created by agrochemicals such as plant fertilizers, pesticides and other plant protection agents, biological alternatives have been developed over the past years. These include biopesticides, such as bacteria for the control of plant diseases, and biofertilizer to improve crop productivity and quality. Especially plant growth promoting rhizobacteria (PGPR) are as effective as pure chemicals in terms of plant growth enhancement and disease control, in addition to their ability to manage abiotic and other stresses in plants. The various facets of these groups of bacteria are treated in this Microbiology Monograph, with emphasis on their emergence in agriculture. Further topics are Bacillus species that excrete peptides and lipopeptides with antifungal, antibacterial and surfactant activity, plant-bacteria-environment interactions, mineral-nutrient exchange, nitrogen assimilation, biofilm formation and cold-tolerant microorganisms.
Dardanelli MS, Carletti SM, Paulucci NS, Medeot DB, Rodriguez Cáceres EA, Vita FA, Bueno M, Fumero MV, Garcia MB: Benefits of Plant Growth Promoting Rhizobacteria (PGPR) and Rhizobia in Agriculture -- Márcia do Vale Barreto Figueiredo, Lucy Seldin, Fabio Fernando de Araujo, Rosa de Lima Eamos Mariano: PGPR: Fundamentals and Applications -- Haluk Ça?lar Kaymak: Potential of PGPR in Agricultural Innovations -- G Seneviratne, MLMAW Weerasekara, KACN Seneviratne, JS Zavahir, ML Kecskés, IR Kennedy: Importance of biofilm formation in plant growth promoting rhizobacterial action -- Naveen K. Arora, Ekta Khare, Dinesh K. Maheshwari: PGPR: Constraints in Bioformulation, Commercialization and Future Strategies -- C.S. Quan, X. Wang, S.D. Fan: Antifungal Compounds of Plant Growth Promoting Rhizobacteria and its Action Mode -- Mohd. Sayeed Akhtar, Zaki A. Siddiqui: Role of Plant Growth Promoting Rhizobacteria in Biocontrol of Plant Diseases and Sustainable Agriculture -- Correa Olga Susana, Soria Marcelo Abel: Potential of Bacilli for Biocontrol and their Exploitation in Sustainable Agriculture -- Nico Labuschagne, T Pretorius, Idris A H: Plant Growth Promoting Rhizobacteria as Biocontrol Agents against Soilborne Plant Diseases -- Piyush Pandey, Abhinav Aeron, Dinesh Kumar Maheshwari: Sustainable Approaches for Biological Control of Fusarium Wilt in Pigeon Pea (Cajanus cajan L. Millspaugh) -- Suikinai Nobre Santos, Vanessa Nessner Kavamura, João Luiz da Silva, Itamar Soares de Melo, Fernando Dini Andreote: Plant Growth Promoter Rhizobacteria in Plants Inhabiting Harsh Tropical Environments and its Role in Agricultural Improvements -- Pankaj Kumar Mishra, Piyush Joshi, Shekhar Chandra Bisht, Jaideep Kumar Bisht, Govindan Selvakumar: Cold tolerant Agriculturally Important Microorganisms -- Stephen P. Cummings, Caroline Orr: The Role of Plant Growth Promoting Rhizobacteria in Sustainable and Low Input Graminaceous Crop Production -- Janpem Prakamhang, Nantakorn Boonkerd, Neung Teaumroong: Rice Endophytic Diazotrophic Bacteria -- Venkadasamy Govindasamy, Murugesan Senthilkumar, Vellaichamy Magheshwaran, Upendra Kumar, Pranita Bose, Vikas Sharma and Kannepalli Annapurna: Bacillus and Paenibacillus spp.: Potential PGPR for Sustainable Agriculture -- Meenu Saraf, Chaitanya Kumar Jha, Dhara Patel: The Role of ACC Deaminase Producing PGPR in Sustainable Agriculture -- Vincent Gray: The Role on the C: N: P Stoichiometry in the Carbon Balance Dynamics of the Legume-AMF-Rhizobium Tripartite Symbiotic Association -- Marieta Hristozkova, Maria Geneva, Ira Stancheva: Regulation of Nitrogen Assimilation in Foliar Fed Legume Plants at Insufficient Molybdenum Supply.
Electronic reproduction.
Keywords: Plant growth-promoting rhizobacteria; Rhizobiaceae; Electronic books